Herramienta para la definición de la orientación estratégica de la innovación para organizaciones (2022)
As the main objective, a tool was designed that facilitates the definition of the strategic orientation focused on innovation in organizations. The search for information was carried out mainly focused on the fundamental contributions for the strategic development of the organizations defined by some authors. An integrative tool was built that allows evaluating the general situation of the company and delivering results that facilitate the orientation of strategic innovation decision making. Finally, knowing that the strategic definition is a difficult process to specify in organizations, this tool allows, through questions, to determine the answer for each aspect or component of the company, delivering a result that is close to the reality of the company. business.